2024
DOI: 10.18632/aging.205375
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of sarcopenia and myosteatosis in trans-arterial (chemo)-embolization treated HCC patients

Jing Long,
Xin Zhang,
Wei Mi
et al.

Abstract: Background: We conducted a meta-analysis to provide evidence-based results for the predictive values of sarcopenia, skeletal muscle index, psoas muscle index and the myosteatosis regarding the impact of survival outcomes and tumor response in patients treated by trans-arterial (chemo)-embolization (TAE/TACE), thereby optimizing therapeutic strategies and maximizing clinical benefits for hepatocellular carcinoma patients. Methods: Qualified studies were retrieved from PubMed, the Cochrane Library, EMBASE, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although the authors found that myosteatosis was predictive of a poor outcome in HCC patients (HR 1.88 95% CI 1.40–2.52, p < 0.0001), no further data on the characteristics of these patients were provided, no subgroup analysis was performed, while the association between myosteatosis with other outcomes was not assessed. A more recent meta-analysis evaluated the prognostic impact of sarcopenia and myosteatosis on HCC patients treated with TACE [ 36 ]: although sarcopenia was associated with a poor outcome, no significant association was demonstrated between the presence of myosteatosis and overall survival (HR: 1.29, 95% CI: 0.74–2.25, p = 0.366). However, in this meta-analysis [ 36 ], only two studies that examined myosteatosis were included and all HCC patients underwent TACE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the authors found that myosteatosis was predictive of a poor outcome in HCC patients (HR 1.88 95% CI 1.40–2.52, p < 0.0001), no further data on the characteristics of these patients were provided, no subgroup analysis was performed, while the association between myosteatosis with other outcomes was not assessed. A more recent meta-analysis evaluated the prognostic impact of sarcopenia and myosteatosis on HCC patients treated with TACE [ 36 ]: although sarcopenia was associated with a poor outcome, no significant association was demonstrated between the presence of myosteatosis and overall survival (HR: 1.29, 95% CI: 0.74–2.25, p = 0.366). However, in this meta-analysis [ 36 ], only two studies that examined myosteatosis were included and all HCC patients underwent TACE.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent meta-analysis evaluated the prognostic impact of sarcopenia and myosteatosis on HCC patients treated with TACE [ 36 ]: although sarcopenia was associated with a poor outcome, no significant association was demonstrated between the presence of myosteatosis and overall survival (HR: 1.29, 95% CI: 0.74–2.25, p = 0.366). However, in this meta-analysis [ 36 ], only two studies that examined myosteatosis were included and all HCC patients underwent TACE. Furthermore, similar to the previous meta-analysis [ 4 ], several limitations could be mentioned, since no assessment of other outcomes was performed, while further subgroup analyses were not provided.…”
Section: Discussionmentioning
confidence: 99%